Interoceptive Accuracy as a Function of Hypnotizability. Issue 4 (2nd October 2021) - Rosati, Anna; Belcari, Iacopo; Santarcangelo, Enrica L.; Sebastiani, Laura
ABSTRACT: This study aimed to measure the interoceptive accuracy (IA) of individuals with high (highs ), medium (mediums), and low hypnotizability (lows) through the heartbeat-counting task during 3 relaxation trials. Participants completed the Multidimensional Assessment of Interoceptive Awareness (MAIA), ECG and skin conductance (SC) were monitored, and the experienced difficulty in counting was reported. Results showed similar counting difficulty and number of actual heartbeats in highs, mediums, and lows. SC decreased in highs during all trials, in mediums and lows only in the third trial. IA measured as [1 – (ǀrecorded heartbeats–counted heartbeatsǀ)/recorded heartbeats] was negatively correlated with hypnotizability and not correlated with interoceptive sensitivity (IS) measured by MAIA scales. Among mediums, IA was higher in males than in females.